Stone Vessels in the Levant - Sparks, RachaelThyrza (Taylor and Francis, 2007)
Cover -- Dedication -- Title -- Copyright -- Contents -- Acknowledgements -- List of Illustrations -- List of Tables -- CHAPTER ONE INTRODUCTION -- 1 'On the backs of giants': previous stone vessel research -- 2 Defining the research parameters -- 3 Problems inherent in the dataset -- 4 A longer than usual life-cycle: the impact of heirlooms and tomb looting on vessel chronology -- 5 Inscribed stone vessels: blessing or curse? -- CHAPTER TWO IMPORTED STONE VESSELS -- 1 Minoan stone vessels -- 1.1 Minoan forms found in the Levant -- 1.1.1 Lamps -- 1.1.2 Tables -- 1.1.3 Cups -- 1.1.4 Small bowls or jars -- 1.1.5 Fragmentary examples of possible Minoan origin -- 1.2 Minoan decorative elements -- 1.3 The significance of Minoan imports in the levant -- 2 Cypriot stone vessels -- 3 Egyptian stone vessels -- 3.1 Egyptian forms found in the Levant -- 3.1.1 Rectangular palettes -- 3.1.2 Plates -- 3.1.3 Bowls -- 3.1.3.1 Hemispherical bowls -- 3.1.3.2 Carinated bowls -- 3.1.3.3. Zoomorphic bowls -- 3.1.4 'Swimming-girl' spoons -- 3.1.5 Pyxides -- 3.1.6 Tazze -- 3.1.7 Goblets -- 3.1.8 Alabastra -- 3.1.8.1 Drop-shaped alabastra -- 3.1.8.2 Conical alabastra -- 3.1.8.2.1 Conical alabastra with funnel-shaped mouths -- 3.1.8.2.2 Conical alabastra with broad flat-topped rim -- 3.1.8.2.3 Conical alabastra with lug handles above rim -- 3.1.8.2.4 Fragmentary conical alabastra -- 3.1.9 Jugs and juglets -- 3.1.9.1 High shouldered juglets (type 1) -- 3.1.9.2 Dipper juglets (type 2) -- 3.1.9.3 Juglets with alabastra-shaped bodies (type 3) -- 3.1.9.4 Juglets imitating Cypriot base-ring ware (type 4) -- 3.1.9.5 Ovoid juglets (type 5) -- 3.1.9.6. Piriform juglets (type 6) -- 3.1.9.7 Broad-mouthed jugs (type 7) -- 3.1.10 Stirrup jars -- 3.1.11 Flasks -- 3.1.12 Pilgrim flasks -- 3.1.13 Tube jars -- 3.1.13.1 Simple tube with upright sides (type 1)